2017
DOI: 10.1038/s41598-017-15733-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition activity of a traditional Chinese herbal formula Huang-Lian-Jie-Du-Tang and its major components found in its plasma profile on neuraminidase-1

Abstract: Huang-Lian-Jie-Du-Tang (HLJDT), a traditional formula with four TCM herbs, has been used for hundred years for different diseases. The current study aimed to assess the inhibitory activity of HLJDT against H1N1 neuraminidase (NA-1), and identify potent NA-1 inhibitors from its plasma profile. The in vitro NA-1 study has shown that the water extract of HLJDT potently inhibited NA-1 (IC50 = 112.6 μg/ml; Ki = 55.6 μg/ml) in a competitive mode. The IC50 values of the water extracts of its four herbs were as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…However, they have significant gastrointestinal intolerance , nightmare and other undesirable side effects. Therefore, during the past few decades, many researchers have focused on the expansion of traditional herb medicines such as San‐Huang‐Xie‐Xin‐Tang and Huang‐Lian‐Jie‐Du‐Tang due to their lasting efficacies and few side effects in the treatment of T2DM, and these multi‐herb prescriptions often include special herb pair such as Scutellariae Radix (SR) and Coptidis Rhizoma (CR). Herb pairs are much simpler than complicated multi‐herb prescriptions and retain the basic therapeutic features.…”
Section: Introductionmentioning
confidence: 99%
“…However, they have significant gastrointestinal intolerance , nightmare and other undesirable side effects. Therefore, during the past few decades, many researchers have focused on the expansion of traditional herb medicines such as San‐Huang‐Xie‐Xin‐Tang and Huang‐Lian‐Jie‐Du‐Tang due to their lasting efficacies and few side effects in the treatment of T2DM, and these multi‐herb prescriptions often include special herb pair such as Scutellariae Radix (SR) and Coptidis Rhizoma (CR). Herb pairs are much simpler than complicated multi‐herb prescriptions and retain the basic therapeutic features.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies of Zhou, Li, Shi, et al (), they predicted LD 50 value for PLT calculated by the rotox program under in silico conditions showed significant PLT toxicity with a value of 410 mg/kg with 69% prediction accuracy.…”
Section: Toxicitymentioning
confidence: 99%
“…Urease inhibition (IC 50 = 0.53 ± 0.01 mM), probably occurred after PLT binding to the sulfhydryl group of the active enzyme center. Interestingly, with the decreasing pH of the environment, the MIC value decreased (Zhou, Li, Shi, et al, ). Owing to its protective and antimicrobial properties, PLT can be successfully used in the treatment of stomach ulcers and gastritis caused by Helicobacter pylori (Jung, Choi, & Jeong, ).…”
Section: Pharmacology Of Pltmentioning
confidence: 99%
“…Glutathione and carnosine were significantly increased after HLJDD and the combination treatment. Metabolomics analysis revealed that HLJDD had better APPswe/PS1dE9 mice Ameliorating neuroinflammation and sphingolipid metabolic disorder [34] HEK 293 cells Inhibiting indoleamine 2,3-dioxygenase activity [133] Anti-infection Candida albicans Inhibiting formation of hyphae and colony morphologies through downregulating the expression of HWP1, ALS3, UME6 and CSH1 [136] Pseudomonas aeruginosa Reducing pyocyanin pigment, elastolytic activity, proteolytic activity, biofilm formation, and bacterial motility [137] H1N1 Inhibiting NA activity [139] Modulation of microbiota High-fat diet and streptozotocin-induced T2DM rats Ameliorating hyperglycemia and restoring the disturbed gut microbiota structure and function through increasing short chain fatty acids-producing bacteria while reducing conditioned pathogenic bacteria [143] anti-inflammatory, anti-bacterial, and anti-oxidative effects than berberine alone. The single use of berberine had an inferior ability to HLJDD in restoring the whole disturbed metabolism of model rats [105].…”
Section: Hepatoprotectionmentioning
confidence: 99%
“…In Mugil cephalus, 1% modified HLJDD feeding for 28 days may prevent Lactococcus garvieae infection and could be used in aquaculture industries [138]. Moreover, the water extracts of HLJDD and its four herbs exerted potent treatment power on H1N1 infection through the inhibition of neuraminidase (NA) activity [139], which is one of the biomarkers Fig. 7 Molecular mechanism of HHLJDD in treating CNS diseases for subtype classification of influenza A virus.…”
Section: Anti-infection and Microbiota-modulatingmentioning
confidence: 99%